2022
DOI: 10.1186/s13287-022-03018-4
|View full text |Cite
|
Sign up to set email alerts
|

MiR-152-5p suppresses osteogenic differentiation of mandible mesenchymal stem cells by regulating ATG14-mediated autophagy

Abstract: Background Osteoporosis affects the mandible resulting in bone loss. Though impairments are not life threatening, they affect a person's quality-of-life particularly vulnerable elderly. MicroRNAs (miRNAs) are novel regulatory factors that play an important role in regulating bone metabolism. Autophagy is evolutionarily conserved intracellular self-degradation process and is vital in the maintenance of both miRNA and bone homeostasis. However, the role of autophagy in the pathogenesis of miRNA r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Noteworthy, either pathological or environmental hypoxia is considered to influence bone health, 40 and intermittent hypoxia can decrease bone mineral density in the mandible of growing rats 41 . Moreover, evidences have shown that autophagy activity was associated with osteogenic differentiation, 42 and autophagy can inhibit osteogenic differentiation of cells from mandible 43 . Therefore, we wanted to know if hypoxia could affect the autophagy and osteogenic differentiation and participate in the pathogenesis of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noteworthy, either pathological or environmental hypoxia is considered to influence bone health, 40 and intermittent hypoxia can decrease bone mineral density in the mandible of growing rats 41 . Moreover, evidences have shown that autophagy activity was associated with osteogenic differentiation, 42 and autophagy can inhibit osteogenic differentiation of cells from mandible 43 . Therefore, we wanted to know if hypoxia could affect the autophagy and osteogenic differentiation and participate in the pathogenesis of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…41 Moreover, evidences have shown that autophagy activity was associated with osteogenic differentiation, 42 and autophagy can inhibit osteogenic differentiation of cells from mandible. 43 Therefore, we wanted to know if hypoxia could affect the autophagy and osteogenic differentiation and participate in the pathogenesis of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“… 176 , 178 , 179 Additionally, in conditions like osteoporosis and osteoarthritis, abnormal DNA methylation affects autophagy, highlighting its role in bone health. 180 …”
Section: Epigenetic Regulation Of Autophagy In Bone Metabolismmentioning
confidence: 99%
“…Moreover, miR-100 reduction accelerates bone regeneration defects of BMSCs in osteoporotic mice by the AKT-mammalian target of rapamycin (mTOR) pathway. 252 Li et al 253 revealed that miR-152-5p is increased in MMSCs-M, and they observed autophagy-related genes, proteins, and autophagosomes in the ovariectomy (OVX) group. They found that downregulating miR-152-5p facilitates the osteogenic differentiation of MMSCs-M through accelerating autophagy-related protein homologue 14 (ATG14)-mediated autophagy with reduced accumulation of endogenous ROS.…”
Section: The Role Of Mirnas In Metabolic Diseasementioning
confidence: 99%
“…They found that downregulating miR-152-5p facilitates the osteogenic differentiation of MMSCs-M through accelerating autophagy-related protein homologue 14 (ATG14)-mediated autophagy with reduced accumulation of endogenous ROS. 253 The balance between osteoblasts and osteoclasts is crucial for bone metabolism. A recent study indicated that delivering recombinant adeno-associated viral (rAAV) vectors to bone and modulating the expression of miR-214-3p and miR-34a-5p can influence both osteoblasts and osteoclasts to treat osteoporosis.…”
Section: The Role Of Mirnas In Metabolic Diseasementioning
confidence: 99%